Rabies in Two Bison from Colorado. (11th June 2013) - Rhyan, Jack C.; Van Campen, Hana; McCollum, Matt; Nol, Pauline; Davis, Rolan; Barfield, Jennifer P.; Salman, Mo
Abstract : Two adult female bison, housed in an outdoor research facility and observed daily, died suddenly three days apart. Minimal coordination and behavioral changes were observed in one animal the evening before being found in a moribund state. Malignant catarrhal fever was suspected in both bison due to a recent confirmed MCF case with similar course. The cause of death was not apparent from necropsy, but brains of both animals were strongly positive for rabies virus antigen by fluorescent antibody and/or immunohistochemical tests. Minimal to mild encephalitis with Negri bodies was observed on histopathology. The bison were located in an area that had not been endemic for skunk rabies; however, a case of rabies in a skunk had been discovered 1.6 km north of the bison paddock two months prior to the bison cases.